Clinically silent Crohn's disease in a patient with Takayasu's Arteritis unresponsive to conventional therapies - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (SPRINGER HEIDELBERG, 2013)
Takayasu arteritis (TA) and Crohn's disease (CD) are chronic inflammatory diseases with granulomatous nature. Here, we report a case of TA with a silent course of CD who was refractory to corticosteroid and immunosuppressive treatments and improved with adalimumab therapy.
Keywords: Takayasu; Crohn's disease; Adalimumab; ASSOCIATION; INFLIXIMAB